In Vitro Characterization of High Purity Factor IX Concentrates for the Treatment of Hemophilia B - Limentani, Steven A; Gowell, Kerry P; Deitcher, Steven R (Thrombosis and Haemostasis, 1995)
This study employed sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis and immunoblotting to assess the purity of seven high purity factor IX concentrates: Aimafix (Aima), AlphaNine-SD (Alpha Therapeutic), Factor IX VHP (Biotransfusion), Immunine (Immuno), Mononine (Armour Pharmaceutical), Nanotiv (Kabi Pharmacia), and 9MC (Blood Products Laboratory). The mean specific activity of these products ranged from 68 U factor IX/mg (Aimafix) to 246 U factor IX/mg (Mononine). SDS-PAGE analysis showed that the highest purity product, Mononine, had a single contaminating band under non-reducing conditions. Two additional bands were detected when this product was analyzed under reducing conditions. All other products had multiple contaminating bands that were more apparent under reducing than non-reducing conditions. The immunoblot for factor IX showed a dominant factor IX band for all products. In addition, visible light chain of factor IX was detected for AlphaNine-SD, Factor IX VHP, Immunine, Mononine, Nanotiv, and 9MC, suggesting that the factor IX in these products had undergone partial activation to factor IXa. Another contaminating band was visible at 49,500 for all of the products except 9MC. In addition to this band, high molecular weight contaminants were apparent for some products, most notably AlphaNine-SD. The identity of these bands is unknown. Immunoblotting failed to demonstrate factor VII as a contaminant of any of the high purity products, although factor Vila could be detected in some lots of Immunine, Nanotiv, and 9MC by a clot-based assay. Factor X contaminated Aimafix, AlphaNine-SD, Factor IX VHP, Immunine, Nanotiv, and 9MC, but activation products of factor X were not detected. Prothrombin contaminated all of the products except Mononine. Activation products of prothrombin were identified for three of four lots of Immunine and for one lot of Factor IX VHP. These results thus demonstrate that high purity factor IX concentrates differ substantially in the degree to which they are contaminated by potentially thrombogenic materials.